Breaking images. Aesthetic activism in anti-speciesist movements in Italy - Lampredi, Giacomo (SocietàMutamentoPolitica, 2024)
This article discusses some results emerging from qualitative social research about anti-speciesist aesthetic activism in Turin and Verona (Italy). Such activism aims to provoke moral-affective ruptures through the visibility of animal suffering. The social movements under examination are involved in call-to-responsibility action, through affective rupture. Some affective manifestations can be performed, under certain circumstances, as real acts of disruption. These acts aim to break consolidated and habitual ways of creating morality. This work will describe the so-called “funeral rituals” of these social movements and how these are employed to communicate the social and structural causes of the systemic killing of animals. Being a vegan activist often means being a source of disturbance, annoyance and discomfort for others, but also of curiosity and wonder. The research was carried out by using multiple ethnographic and qualitative methods to provide a deep analysis of the processual and relational aspects of this form of aesthetic activism.